Thomas Carlyle’s Defense of Prophet Muhammad SAW: A Critical Discourse Analysis in Da’wah Communication Perspective - Afidatul Asmar; St. Aminah; Ramli; Nurhikmah; Dian Adi Perdana (Palakka : Media and Islamic Communication, 2025)
This study examines Thomas Carlyle’s defense of Prophet Muhammad SAW as articulated in his lecture On Heroes, Hero-Worship, and the Heroic in History (1840). At a time when Western society was dominated by negative stereotypes and prejudice against Islam, Carlyle presented a counter-narrative by portraying Prophet Muhammad SAW as a sincere, moral, and heroic figure. Using a qualitative approach with Critical Discourse Analysis based on Norman Fairclough’s model, this research analyzes the text at three levels: textual representation, discursive practice, and social practice. The findings reveal that Carlyle’s discourse challenges dominant Western narratives by reconstructing the image of Prophet Muhammad SAW through ethical leadership, spiritual authenticity, and historical legitimacy. From the perspective of da’wah communication, Carlyle’s discourse functions as a form of intellectual mediation that promotes intercultural understanding and counters Islamophobic narratives. This study contributes to the field of Islamic communication by highlighting the role of intellectual discourse as an alternative medium of da’wah in shaping public perception and fostering cross-cultural dialogue.